Modelling Export Prices and Quantities in a Small Open Economy - Browne, Francis X. (The Review of Economics and Statistics, 1982)
volvement by U.S. Manufacturing Industry, OxfJord Economic Papers 32 (Mar. 1980), 102-122. Lindenberg, Eric B., and Stephen A. Ross, Tobin's q Ratio and Industrial Organization, Journal of Business 54 (Jan. 1981), 1-32. Marvel, Howard P., Foreign Trade and Domestic Competition, Economic Inquiry 18 (Jan. 1980), 103-122. Thomadakis, Stavros B., A Value-Based Test of Profitability and Market Structure, this REVIEW 59 (May 1977), 179-185.